Enhancing the egg's natural defence against bacterial penetration by increasing cuticle deposition. (10th July 2013) - Bain, M. M.; Mcdade, K.; Burchmore, R.; Law, A.; Wilson, P. W.; Schmutz, M.; Preisinger, R.; Dunn, I. C.
Summary: The cuticle is a proteinaceous layer covering the avian egg and is believed to form a defence to microorganism ingress. In birds that lay eggs in challenging environments, the cuticle is thicker, suggesting evolutionary pressure; however, in poultry, selection pressure for this trait has been removed because of artificial incubation. This study aimed to quantify cuticle deposition and to estimate its genetic parameters and its role on trans‐shell penetration of bacteria. Additionally, cuticle proteins were characterised to establish whether alleles for these genes explained variation in deposition. A novel and reliable quantification was achieved using the difference in reflectance of the egg at 650 nm before and after staining with a specific dye. The heritability of this novel measurement was moderate (0.27), and bacteria penetration was dependent on the natural variation in cuticle deposition. Eggs with the best cuticle were never penetrated by bacteria ( P < 0.001). The cuticle proteome consisted of six major proteins. A significant association was found between alleles of one of these protein genes, ovocleidin‐116 ( MEPE ), and cuticle deposition ( P = 0.015) and also between alleles of estrogen receptor 1 ( ESR1 ) gene and cuticle deposition ( P = 0.008). With the heritability observed, genetic selection should be possible to increase cuticle deposition in commercial poultry, so reducing trans‐generational transmission of microorganisms and reversing the lack of selection pressure for this trait during recent domestication.